Replacement of anticodon loop nucleotides to produce functional tRNAs: amber suppressors derived from yeast tRNAPhe. - Bruce, A G (1982)
The method of anticodon loop replacement has been used to make derivatives of yeast tRNAPhe. By constructing tRNAs with a CUA anticodon, complementary to the amber (UAG) terminator, functional amber suppressor tRNAs were produced. The activity of these tRNAs was assayed in a mammalian cell-free protein synthesizing system. The level of suppression reflects the efficiency of codon recognition. tRNAs were constructed with either A, C, U, or G on the 3' side of the CUA anticodon. The tRNAs containing the purines were efficient amber suppressors, whereas those containing pyrimidines were inefficient.